2017
DOI: 10.3389/fpls.2017.01099
|View full text |Cite
|
Sign up to set email alerts
|

A FERONIA-Like Receptor Kinase Regulates Strawberry (Fragaria × ananassa) Fruit Ripening and Quality Formation

Abstract: Ripening of fleshy fruits is controlled by a series of intricate signaling processes. Here, we report a FERONIA/FER-like receptor kinase, FaMRLK47, that regulates both strawberry (Fragaria × ananassa) fruit ripening and quality formation. Overexpression and RNAi-mediated downregulation of FaMRLK47 delayed and accelerated fruit ripening, respectively. We showed that FaMRLK47 physically interacts with FaABI1, a negative regulator of abscisic acid (ABA) signaling, and demonstrated that FaMRLK47 regulates fruit ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 71 publications
3
36
0
Order By: Relevance
“…Studies investigating fruit ripening in strawberry have mainly focused on the mechanisms regulating anthocyanin accumulation ( Jiang and Joyce, 2003 ; Medina-Puche et al , 2014 ; Lin-Wang et al , 2014 ; Kadomura-Ishikawa et al , 2015 ). Several important regulatory proteins involved in anthocyanin accumulation have been identified, such as the protein kinases FaSnRK2.6 and FaMRLK47 and the transcription factors FaMYB1 and FaMYB10 ( Aharoni et al , 2001 ; Medina-Puche et al , 2014 ; Lin-Wang et al , 2014 ; Han et al , 2015 ; Kadomura-Ishikawa et al , 2015 ; Jia et al , 2017 ). We recently found that FaMRLK47, a negative regulator of anthocyanin accumulation, also functions as a positive regulator of sugar accumulation and that two important structural genes involved in sucrose accumulation, FaSPS3 (sucrose-6-phosphate synthase 3, gene31122 ) and FaSUS1 (sucrose synthase 1, gene12940 ), are key structural genes downstream of FaMRLK47 ( Jia et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating fruit ripening in strawberry have mainly focused on the mechanisms regulating anthocyanin accumulation ( Jiang and Joyce, 2003 ; Medina-Puche et al , 2014 ; Lin-Wang et al , 2014 ; Kadomura-Ishikawa et al , 2015 ). Several important regulatory proteins involved in anthocyanin accumulation have been identified, such as the protein kinases FaSnRK2.6 and FaMRLK47 and the transcription factors FaMYB1 and FaMYB10 ( Aharoni et al , 2001 ; Medina-Puche et al , 2014 ; Lin-Wang et al , 2014 ; Han et al , 2015 ; Kadomura-Ishikawa et al , 2015 ; Jia et al , 2017 ). We recently found that FaMRLK47, a negative regulator of anthocyanin accumulation, also functions as a positive regulator of sugar accumulation and that two important structural genes involved in sucrose accumulation, FaSPS3 (sucrose-6-phosphate synthase 3, gene31122 ) and FaSUS1 (sucrose synthase 1, gene12940 ), are key structural genes downstream of FaMRLK47 ( Jia et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…the MRLK mostly expressed in Fxa fruits [56] and with the Fxa LLG2 homolog (maker-Fvb3-4-snap-gene-34.65), show that the structural components necessary to bind MRLK47 and LLG2 are conserved in FanRALF3 (Fig 4B and 4C), suggesting a similar binding mechanism and complex formation. In Arabidopsis, AtRALF23 binding to FERONIA and LLG proteins leads to negative immunity response regulation, and this hypothesis can be tested by analysis of FanRALF3-1 binding to MRLK47 in fruits.…”
Section: Plos Onementioning
confidence: 89%
“…In a recent work, Jia et al [56] analyzed the expression of the woodland strawberry (F. vesca) Malectin Receptor Like Kinases (MRLK) also known as the Catharanthus roseus RLKlike proteins (RLK1Ls). F. vesca MRLKs are encoded by more than 60 genes, and more than 50% of these are expressed during fruit development.…”
Section: Plos Onementioning
confidence: 99%
“…Homology models of FaRALF3, in complex with FERONIA and LLG2 were generated using Modeller [49](v9.19) package using the complex of A. thaliana RALF23, LLG2 and FERONIA (PDB: 6a5e) as the template. ClustalX was used to create alignments of different components of the complex: FaRALF3 (GDR: snap_masked-Fvb2-2-processed-gene-47.50-mRNA-1), Fragaria x ananassa FERONIA MRLK47 (GDR: Uniprot: A0A1J0F5V4) and Fragaria x ananassa LLG2 (GDR: maker-Fvb3-4-snap-gene-34.65-mRNA-1) with the A. thaliana proteins in the A. thaliana complex.…”
Section: Methodsmentioning
confidence: 99%